Carga sellada - Vargas-Weise, Julia; Lechín Weise, Juan Claudio, 1956-; Sánchez Parra, Gustavo; Cubero, Gonzalo (Actor); Bredow, Luis (Imagina Films, 2015)
When a cargo of toxic waste from abroad is discovered in a small Andean village, the government decides to surreptitiously move it via an old train. However, the ragtag group carrying the load -- an ambitious police captain, an old anarchist train conductor, three policemen and a runaway girl -- are confronted by a population savvy to their plot. Three days turns to three weeks, the press turns it into a media scandal, and the government turns its back on them. The group is forced to deal with their fate.